The influence of culture on perception of fairness on assessment centres for staff selection - Mohd Hanafiah, Ahmad; Ab Hamid, M. R.; Ida Rizyani, Tahir; Noor Azlinna, Azizan (2017)
Assessment centres (ACs) are a popular technique that has been used and studied for at least 50 years, primarily in Western countries. ACs are used to facilitate human resource decisions, such as selection and promotion decisions, diagnosing training needs, and facilitating employee development. The proliferation of ACs around the world has raised questions about their application in specific countries. Although a number of studies have found that differences in cultural settings across countries may have an impact on human resource practices and strategies, very little attention has been given specifically to ACs. As the AC approach has also been used in developing countries such as Malaysia, it is important to understand how these factors in different cultural settings may influence the implementation of ACs and how this might differ from its implementation in more developed nations. Therefore, this study aims to respond to this research gap and contribute to the body of knowledge in this area by exploring the implementation of ACs in Malaysia, as an example of an Eastern, and developing country. Using the model of cultural fit and organisational justice theory, this study aims to explore how the national culture may influence the design and implementation of assessment centres in Malaysian public sectors. This exploratory study involves two stages of data collection, semi-structured interviews, and survey questionnaires. The respondents for the first study (semi-structured interview) are personnel who have had experience as developer/assessors, and also those who have had experience as participants, in ACs in various ministries in Malaysia. The first study aims to explore how assessors and participants perceive the design, scoring methods, and feedback associated with traditional approach dimension-based assessment centres and alternative approach task-based assessment centres and how culture influence the process. For the second study (survey questionnaires), the respondents are from those who have had experience as participants. In total, a survey of 405 respondents was successfully carried out and 381 useful feedbacks were analysed. This second study utilises organisational justice theory in exploring participants’ reactions to the fairness of ACs design, implementation and outcomes. This organisational justice consist of distributive justice rules and 10 procedural justice rules that fall under three broad categories were tested. A total of thirteen hypotheses have been put forward to test the relationships amongst the culture values, distributive justice latent, three categories under procedural justice, and outcome after attending ACs. Structural Equation Modelling (SEM) with SmartPLS software using Partial Least Squares (PLS) estimation is used for modelling analysis. Findings from the first study showed that Malaysia is a society that put emphasis on working in group, and accept the importance of power distance, and rely on high communication context. These socio-cultural findings reflect the internal work culture which focus more on working in group, maintaining harmony, and respect to seniority in decision-making process. Meanwhile, findings for study two showed that collectivism and relationship preferences as the most significant cultural variable in influencing reaction on fairness of ACs. In addition, this study also showed positive outcome related to attitude, affect and recommendation towards ACs. Findings from this research also has closed the gap by highlighting the practice, acceptance and outcome from attending ACs in Malaysian public sector from holistic perspectives which include assessors, participants and module developers.